Analysis of Financial Performance on Shariah Insurance Companies in Indonesia Using Early Warning System (EWS) and Risk Based Capital (RBC) Methods - Ratu Mengge Ayu; Dyah Titis Kusuma Wardani (Universitas Muhammadiyah Yogyakarta, 2023)
This study aims to analyze the financial performance of Sharia Life Insurance companies and Sharia General Insurance companies for the period 2017-2019 using the Early Warning System (EWS) and Risk-Based Capital (RBC) methods. The EWS ratios used in this study are Liquidity Ratios, Capital Adequacy Ratios, Claim Expense Ratios, and Own Retention Ratios. Meanwhile, the RBC method used is based on regulations set by the government. This research was descriptive research with a quantitative approach. The samples used in this study were 5 Sharia Life Insurance companies and 4 Sharia General Insurance companies selected using the purposive sampling method. The results of this study indicate that: First, the financial performance of Sharia Life Insurance companies and Sharia General Insurance companies for the period 2017-2019 were quite good. Second, Sharia General Insurance was slightly better than Sharia Life Insurance. And third almost all research variables showed that there is no significant difference between Sharia Life Insurance and Sharia General Insurance. In the future, Sharia Life Insurance companies and Sharia General Insurance companies are advised to pay more attention to the company’s stability because stability is very important to show the success of an insurance company in running its business.